Assessment of patient dose and radiogenic risks during endoscopic retrograde cholangiopancreatography. (November 2016) - Sulieman, A.; Elzaki, M.; Alkhorayef, M.; Babikir, E.; Abuzaid, M.; Dalton, A.; Bradley, D.
Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) is an invasive technique that has been used for over 30 years in the diagnosis and management of pancreaticobiliary disorders. The objectives of this study were to evaluate the patient entrance surface air kerma doses (ESAK) and estimate the organ and effective doses during ERCP in three hospitals in Khartoum. A total of 55 patients were examined in three hospitals in Khartoum state, Sudan. Calibrated thermoluinescent dosimeters (TLD) were used to measure patients' ESAK. Organ and effective doses were estimated using National Radiological Protection Board (NRPB) software. The overall mean of ESAK for all ERCP procedures was 42.4 mGy. The mean patient ESAK in Fedail (A), Soba (B) and Ibn sena (C) hospitals were 26.7 mGy, 26.0 mGy and 72.4 mGy, respectively. The effective doses in three hospitals were 1.60, 1.56 and 2.67 mSv in that order and the overall mean effective dose was 1.94 mSv. Patient radiation doses vary widely among the hospitals. Patient ESAK is low compared to previous studies in the light of the current practice. Patient dose was decreased significantly in the last two decades. Highlights: Radiation dose was measured for patients during ERCP procedures. Radiogenic risk per ERCP procedure was estimated. Patient ESAK is low compared to previous studies in the light of the current practice. Patient dose was decreased significantly in the last two decades due to advancement in imaging technology and protocols.